2006
DOI: 10.14429/dsj.56.1905
|View full text |Cite
|
Sign up to set email alerts
|

Transition Metal Carbohydrazide Nitrates: Burn-rate Modifiers for Propellants

Abstract: This paper discusses the synthesis and characterisation of cobalt (Co), nickel (Ni) and copper (Cu) carbohydrazide nitrates. In differential scanning calorimetry (DSC), the complexes exhibited exothermic decomposition indicating their energetic nature. The commencement of decomposition was observed at 220 °C for Ni complex, and at 160 °C for Co complex whereas that of Cu complex occurred at 75 °C. In view of the better thermal stability, Ni and Co complexes were selected for further study. The activation energ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 6 publications
(4 reference statements)
1
10
0
1
Order By: Relevance
“…; in pharmaceuticals; and as catalyst [53] They are also used in dyes [54], polymers, [54] as well as they are applied in nanotechnology [55], laser [56], transistor [57], in defense as gas generating agents [58], and pyrotechnic mixtures [59]. ; in pharmaceuticals; and as catalyst [53] They are also used in dyes [54], polymers, [54] as well as they are applied in nanotechnology [55], laser [56], transistor [57], in defense as gas generating agents [58], and pyrotechnic mixtures [59].…”
Section: Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…; in pharmaceuticals; and as catalyst [53] They are also used in dyes [54], polymers, [54] as well as they are applied in nanotechnology [55], laser [56], transistor [57], in defense as gas generating agents [58], and pyrotechnic mixtures [59]. ; in pharmaceuticals; and as catalyst [53] They are also used in dyes [54], polymers, [54] as well as they are applied in nanotechnology [55], laser [56], transistor [57], in defense as gas generating agents [58], and pyrotechnic mixtures [59].…”
Section: Applicationsmentioning
confidence: 99%
“…For example some Ni NPs are considered as anode materials for rechargeable batteries, ethanol fuel cell, and a fine substitute for a noble metal used in the internal electrodes of multilayer ceramic capacitors [160]. Bushuyev et al [58] have reported the energetic compounds of type [CuX 2 (C 7 Similarly, some other transition metal complexes Co, Ni, and Zn of carbohydrazide with perchlorate salt were investigated by Talawar et al [162] where they reported that Co and Ni complexes were superior detonants as compared with lead azide and mercuric fulminate in terms of low vulnerability. It is documented that they are used as primary explosives [161e163], burning rate modifiers [57], and also in gas generating agents, [164e166].…”
Section: Scope Of Schiff Bases and Their Complexes For Nanobiotechnologymentioning
confidence: 99%
“…Complexes of carbohydrazide with transition metals such as nickel, cobalt, cadmium, and copper have been studied for a variety of applications including their use as primary explosives, [4][5][6] gas generating agents, [7][8][9] and burning rate modifiers. [10] An alternative application for this class of materials would be flame colorants for use in pyrotechnics. [11][12][13] To this end copper complexes of carbohydrazide should be viable candidates that can be used to generate blue and green flame colors, which are difficult to obtain.…”
Section: Introductionmentioning
confidence: 99%
“…Азотосодержащие энергонасыщенные материалы имеют большое количество связей N-N и C-N и, следовательно, большую положительную теплоту образования. Низкое содержание углерода и водорода в этих соединениях дает тройной положительный эффект: повышает плотность соединений, позволяет легко получить хороший кислородный баланс и производит большее количество молей газообразных продуктов в расчете на 1 грамм энергонасыщенных материалов [12]. Гидразины, азиды, тетразолы, содержащие большое количество азота, могут быть использованы в качестве энергонасыщенных материалов.…”
Section: вступлениеunclassified